How to Teach Adults : Plan Your Class, Teach Your Students, Change the World - Spalding, Dan. (San Francisco, CA : Jossey-Bass, a Wiley Brand, 2014)
'Your hands-on guide to teaching adults. no matter what the subjectIn this expanded edition of How to Teach Adults, Dan Spalding offers practical teaching and classroom management suggestions that are designed for anyone who works with adult learners, particularly new faculty, adjuncts, those in community colleges, ESL teachers, and graduate students. This reader-friendly resource covers all phases of the teaching process from planning what to teach, to managing a classroom, to growing as a professional in the field.How to Teach Adults can guide new instructors who are trying to get up to speed on their own or can help teacher trainers cover what their students need to know before they get in front of a class. It is filled with down-to-earth tips and checklists on such topics as connecting with adult students, facilitating discussions, and writing tests, plus everything you need to remember to put into your syllabus and how to choose the right textbook. Dan Spalding reveals what it takes to teach all students the skills they need to learn, no matter what the topic or subject matter.Full of vivid examples from real-world classrooms, this edition: Shows how to get started and tips for designing your course Includes information for creating a solid lesson plan Gives suggestions for developing your teacher persona How to Teach Adults offers the framework, ideas, and tools needed to conduct your class or workshop with confidence'--
Preface -- Acknowledgments -- About the author -- Foundations of teaching -- How to get started teaching -- How to design your course -- How to lesson plan -- Grading and assessments -- How to run your class -- How to present information -- How to develop your teacher persona -- Growing as a teacher -- The future of education -- Appendix: Teacher glossary -- References -- Further reading -- Index.
Machine generated contents note: Preface Acknowledgments About the Author 1 Foundations of Teaching 2 How to Get Started Teaching 3 How to Design Your Course 4 How to Lesson Plan 5 Grading and Assessments 6 How to Run Your Class 7 How to Present Information 8 How to Develop Your Teacher Persona 9 Growing as a Teacher 10 The Future of Education Appendix: Teacher Glossary References Further Reading Index .
Includes bibliographical references : (p. 211-213) and index.
Keywords: Adult education teachers -- Training of -- United States; Adult education -- Study and teaching -- United States